1997
DOI: 10.1093/emboj/16.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the papillomavirus E2 protein in HeLa cells leads to apoptosis

Abstract: (Androphy et al., 1987; Dostatni et al., 1988;McBride Sylvain Goyat, Moshe Yaniv and et al., 1989). Franç oise Thierry 1Bovine papillomavirus type 1 (BPV-1) has been studied condylomas. In HPV18, the viral transforming genes E6 level of cell death by apoptosis and G 1 arrest. Overand E7 are expressed from a single promoter, termed P 105 , expression of a p53 trans-dominant-negative mutant which is regulated by an upstream 800 bp long control abolished both E2-induced p53 transcriptional activregion (LCR) (Thie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
214
1
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(229 citation statements)
references
References 61 publications
9
214
1
5
Order By: Relevance
“…In contrast, both mutants induced cell death in around 15% of transfected cells, which was comparable to apoptosis mediated by the wild-type protein (Table 1). In control experiments, overexpression of the truncated E2 protein induced a level of cell death of 5 ± 8% which was also observed with a null control plasmid (data not shown and Desaintes et al, 1997). In conclusion, mutants of the E2TD that do not e ciently activate p53, and consequently do not arrest the cell cycle, are still able to induce cell death, showing that the two functions are genetically separable.…”
Section: Mutations In the Transactivation Domain Of E2 Can Discriminasupporting
confidence: 54%
See 1 more Smart Citation
“…In contrast, both mutants induced cell death in around 15% of transfected cells, which was comparable to apoptosis mediated by the wild-type protein (Table 1). In control experiments, overexpression of the truncated E2 protein induced a level of cell death of 5 ± 8% which was also observed with a null control plasmid (data not shown and Desaintes et al, 1997). In conclusion, mutants of the E2TD that do not e ciently activate p53, and consequently do not arrest the cell cycle, are still able to induce cell death, showing that the two functions are genetically separable.…”
Section: Mutations In the Transactivation Domain Of E2 Can Discriminasupporting
confidence: 54%
“…This induction results partly from transcriptional repression of the endogenous E6 transcription by E2. Repression of E6, that is an inducer of p53 degradation by the ubiquitin pathway, favors accumulation of a transcriptionally active p53 (Hwang et al, 1993(Hwang et al, , 1996Desaintes et al, 1997;Dowhanick et al, 1995). E2-mediated transcriptional repression of E6 requires binding of the viral protein to speci®c recognition sites in the HPV18 early promoter contained within the viral DNA integrated in the HeLa cell genome.…”
Section: Discussionmentioning
confidence: 99%
“…There are other similar examples among viral oncoproteins and cellular oncogenes involved in cell death regulation. The adenovirus E1A, HTLV-1 Tax and human papilloma virus (HPV) E7 proteins stimulate cell proliferation and also cause apoptosis, by both p53-dependent and p53-independent mechanisms (Debbas and White, 1993); Pan and Griep, 1995;Teodoro et al, 1995;Yamada et al, 1994) and the transcriptional regulator E2 of HPV can trigger apoptosis independently of p53 transcriptional activity (Desaintes et al, 1997). Overexpression of c-myc can lead to apoptosis that requires a property intrinsic to p53 in serumstarved ®broblasts, but it may operate through p53-independent pathways in epithelial cells, or during lymphomagenesis (Hsu et al, 1995;Sakamuro et al, 1995;Wagner et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Antiapoptotic stratgegies may be bene®cial for viruses to establish persistent infections, but for less obvious reasons, a number of non-lytic viruses, including HIV, HTLV-1, HPV and HBV have developed pro-apoptotic functions (Desaintes et al, 1997;Westendorp et al, 1995;Yamada et al, 1994). It has been proposed that apoptosis could represent an important step by which such viruses disseminate progeny, by enhancing virus release and spread to new host cells (Teodoro and Branton, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was found that E2 and E7 proteins can induce apoptosis in transformed cells (Cho et al, 2002;Demeret et al, 2003;Desaintes et al, 1997;Webster et al, 2000) and that progesterone and estrogen increase the levels of E2-and E7-induced apoptosis (Webster et al, 2001). Although the mechanism is still not completely understood, the authors suggested that the pro-apoptotic signals from E2 and E7 may be counterbalanced by anti-apoptotic signals from HPV E6 protein.…”
Section: Role Of Sex Hormones In Hpv Gene Expressionmentioning
confidence: 99%